ANALISIS GTVH TERHADAP HUMOR VERBAL DALAM WEB SERIES MALAM MINGGU MIKO OLEH RADITYA DIKA: Array - Febrian, Rizki; Zuindra, Zuindra (Universitas Harapan Medan, 2022)
This research is aimed to analyze the kinds of verbal humor and the application of GTVH (General Theory of Verbal Humor) found in the web series: Malam Minggu Miko, which centered the data in five episodes. The analysis focused on seven kinds of verbal humor by Shade (1996). The next section is the analysis of the verbal humor by adapting the GTVH Knowledge Resources or KR included six parameters which are SO (Script Opposition), LM (Logical Mechanism), SI (Situation), TA (Target), NA (Narrative), and LA (Language). The result of this research shows eleven verbal humor included; two satires, two ironies, two wits, two farces, one pun, one riddle, and one joke. The GTVH analysis by KR’s parameters through the data was also successfully applied in the ten verbal humors found in the web series: Malam Minggu Miko.